Watermarking and Cryptography Based Image Authentication on Reconfigurable Platform - Altaf O. Mulani; P. B. Mane (Institute of Advanced Engineering and Science, 2017)
Now-a-days, multimedia based applications have been developed rapidly. Digital information is easy to process but it allows illegal users to access the data. For protecting the data from this illegal use, Digital Rights Management (DRM) can be used. DRM allows secure exchange of digital data over internet or other electronic media. In this paper, FPGA based implementation of DWT alongwith Advanced Encryption Standard (AES) based watermarking is discussed. With this approach, improved security can be achieved. The complete system is designed using HDL and simulated using Questasim and MATLAB Simulink model. The synthesis result shows that this implementation occupies only 2117 slices and maximum frequency reported for this design is 228.064 MHz.